MARKOVNIKOV ADDITION OF CHLOROSULFURIC ACID TO EUGENOL ISOLATED FROM CLOVE OIL - I Made Sudarma; Emmy Yuanita; I Wayan Suana (Indonesian Journal of Chemistry, 2013)
The objective of this research was to synthesize new compounds with potential biological activity from readily accessed natural products. Eugenol has been reported to posses antioxidant and anticancer properties and was prepared by extracting from clove buds with dichloromethane and followed by isolation using column chromatography to afford pure eugenol (73%). In an attempt to enhance intrinsic activity of this natural compound, some derivatives were possible to synthesize. The main aim of this preliminary research was to transform eugenol to become sulfonic derivative. Eugenol was transformed to its sulfonic derivative in moderate yield (64%) by treatment with chlorosulfuric acid which undergoes Markovnikov addition. This product was rapidly confirmed by GC-MS and NMR analyses. Selective inhibition was performed by cyclic sulfonic ester derivative which could inhibit Eschericia coli and Staphylococcus aureus but not for Bacillus cereus.